1986
DOI: 10.1111/j.1365-2125.1986.tb02934.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity effects on nitrazepam disposition.

Abstract: 1 Nitrazepam pharmacokinetics were studied in 14 obese (mean ± s.e. mean body weight 107 ± 9 kg; percent ideal body weight [IBW] .6 ng ml-1; NS) and time required after drug administration to reach peak concentration (1.52 ± 0.24-obese vs 1.59 ± 0.36 h; NS) indicated no differences between obese and control subjects.3 Elimination half-life was markedly increased in obese subjects (33.5 ± 2.2 vs 23.9 + 1.2 h; P < 0.001) due to increased apparent volume of distribution (Vd) (290 ± 45 vs 137 + 12 l; P < 0.005).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Abernethy and Greenblatt evaluated in several studies the effects of obesity on the disposition of different benzodiazepines, including diazepam, alprazolam, nitrazepam, lorazepam, and midazolam [18,[70][71][72][73]. All of these studies showed a significant increase in both volume of distribution and elimination half-life, with a significant correlation between lipid solubility and the extent of their distribution in the excess fat.…”
Section: Benzodiazepinesmentioning
confidence: 95%
“…Abernethy and Greenblatt evaluated in several studies the effects of obesity on the disposition of different benzodiazepines, including diazepam, alprazolam, nitrazepam, lorazepam, and midazolam [18,[70][71][72][73]. All of these studies showed a significant increase in both volume of distribution and elimination half-life, with a significant correlation between lipid solubility and the extent of their distribution in the excess fat.…”
Section: Benzodiazepinesmentioning
confidence: 95%
“…All clinical protocols were reviewed and approved by the applicable institutional review boards, and all study participants provided written informed consent. Nineteen candidate drugs (Table 1) were administered in single-dose pharmacokinetic studies in healthy young volunteers of "normal weight" [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Excepting imipramine and propranolol, kinetic studies were also conducted in comparison cohorts of otherwise healthy obese subjects matched for age and gender (Table 2).…”
Section: Clinical Pharmacokinetic Studiesmentioning
confidence: 99%
“…Because transporters are responsible for a significant phase of chemical handling, this observed change in transporter expression implies that obese mice should have differential patterns of chemical absorption and elimination. Multiple drugs show altered pharmacokinetics and toxicokinetics in obese patients and the underlying reasons for altered pharmacokinetics in obese patients have not been well defined, but alterations in drug transporter expression could contribute to these observations (Bergman et al, 2007;Edelman et al, 2009). Abernethy et al (1986 reported altered disposition of nitrazepam in obese human subjects.…”
Section: Downloaded Frommentioning
confidence: 99%